High dose chemotherapy with autologous stem cell transplantation in diffuse large B-cell lymphoma - Mey, Ulrich J.M. (German Medical Science GMS Publishing House, 2007)
Background: High-dose chemotherapy (HDT) with autologous stem cell transplantation (ASCT) plays an important role in the treatment of aggressive non-Hodgkin’s lymphoma (NHL). We report on a retrospective analysis of all patients with diffuse large B-cell lymphoma who were consecutively treated with HDT followed by ASCT at the University Hospital of Bonn, Germany, between 1996 and 2004. Methods: A total of 25 patients were transplanted for biopsy-proven diffuse large B-cell lymphoma (DLBCL). Eight patients received up-front HDT as first-line therapy, four patients received HDT due to incomplete response to conventional induction chemotherapy, and six patients were treated for primary refractory disease. Seven patients had recurrent lymphoma. Results: A complete remission (CR) was achieved in 14 of 25 patients (56%). Estimated 3-year survival for patients treated with upfront HDT, chemosensitive patients with incomplete response to first line therapy, and patients with chemosensitive relapsed disease was 87.5%, 50.0% and 60.0%, respectively. In contrast, no patient with primary refractory disease or relapsed disease lacking chemosensitivity lived longer than 8 months. Chemosensitivity was the only significant prognostic factor for overall survival (OS) in multivariate analysis. Conclusions: Our results confirm that HDT and ASCT is a highly effective therapy in patients with DLBCL leading to long-term survival in a substantial proportion of patients. Patients treated upfront for high-risk disease, incomplete response to conventional first-line therapy, or for chemosensitive relapse have a good prognosis. In contrast, patients with primary chemorefractory disease and patients with relapsed disease lacking chemosensitivity do not benefit from HDT with ASCT.